Transcriptome analysis reveals potential regulatory mechanism of genes and pathways following Aeromonas veronii infection and hypoxic stress in Chinese mitten crab, Eriocheir sinensis - Gang Jiang; Fengyuan Yan; Yuanfeng Xu; Jianlin Li; Wenrong Feng; Guo an Hua; Wen jing Li; Jun Zhou; Yongkai Tang (Aquaculture Reports)
Environment hypoxia and Aeromonas veronii infection represent the major physiological challenge for the economic aquaculture species. However, the molecular mechanisms underlying these stresses remain incompletely elucidated. This study focused on evaluating hypoxia stress and A. veronii infection in Eriocheir sinensis, and elucidating the molecular mechanisms via biochemical, histopathological and transcriptomic analyses. 360 healthy E. sinensis were equally divided into four groups: a normoxic control (C) at 7.5 ± 0.5 mg/L DO, a hypoxic treatment (Th) at 1.5 ± 0.5 mg/L DO, an A. veronii-infected group (Tv) at 3.5 × 107 CFU/mL under normal DO conditions, and a dual-stress condition (Thv) combining hypoxia and infection. Results demonstrated significantly elevated levels of antioxidant enzymes (T-AOC, SOD, and CAT), and immune enzymes (AKP, ACP) in treatments Th, Tv, and Thv, with a contrasting decrease in MDA contents. Moreover, structural damage in hepatopancreas and gills, notably vacuolation and lobular membrane thickening among these treatments. Transcriptome analysis highlighted 157, 135 and 161 differentially expressed genes (DEGs) in treatments Th, Tv, and Thv, respectively, relative to C. KEGG pathway analysis indicated these DEGs were predominantly associated with pathways linked to immunity and metabolism. Hypoxia activated genes involved in energy metabolism while down-regulated those related to protein synthesis. A. veronii infection, meanwhile, reduced the expression of genes associated with lipid and nitrogen metabolism. Under dual stress, protein synthesis and lipid metabolism were further repressed, and immune-related gene expression was markedly up-regulated. Notably, hypoxia and A. veronii infection exhibit a synergistic toxic effect on E. sinensis. Finally, 29 DEGs were identified as critical in responding to hypoxia stress and A. veronii infection. These findings contribute to understanding the mechanisms of stress responses in aquatic animals, potentially aiding in the development of strategies to enhance health and productivity in aquaculture.